Germany's social security system under strain - Horst Siebert (Kiel Institute for World Economics (IfW), 2003)
Germany's social security system is surveyed, its benefits and contributions are discussed. The expansion of this system in the last decades is described, its impact on employment and growth is studied and proposals for the reform of the system are discussed.
Keywords: H5; I18; I3; J26; 330; welfare state; health; unemployment and old age insurance; policy reform; social security system; Sozialversicherung; Sozialversicherungsfinanzierung; Öffentliche Sozialausgaben; Sozialstaat; Sozialreform; Deutschland